2021
DOI: 10.1021/acssuschemeng.1c00502
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Waste Tires as Tunable Frameworks for Use in Sodium-Ion and Lithium–Sulfur Batteries

Abstract: Selectively resourcing electrode components can provide a significant advantage in the uptake of next generation battery systems especially considering the performance of currently incumbent lithium-ion battery technology. This work systematically explores the use of a waste stream to generate electrode components and the influence that treatment and preparation factors have on electrochemical performance. A series of carbonaceous materials derived from waste rubber tires are prepared, involving pyrolysis at 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 115 publications
1
26
0
Order By: Relevance
“…Moreover, after further processing [ 68 , 69 ], these activated carbon materials can be employed in a large variety of fields, as depicted in Figure 4 . In recent studies, activated rCB samples were investigated as adsorbents for the separation of compounds in gaseous [ 70 , 71 , 72 ] and liquid [ 73 ] phases (e.g., adsorption of dyes [ 74 , 75 ], organic compounds [ 76 , 77 , 78 , 79 ], and heavy metals [ 80 , 81 , 82 ]), as conductive additives for carbon electrodes of sodium and lithium batteries [ 83 , 84 , 85 , 86 ], as supercapacitors [ 87 ], as catalysts [ 88 , 89 ] and as nanomaterial precursors [ 90 , 91 ]. Even though rCB has been identified as a potential solid fuel (the HHV is within 25 to 34 MJ/kg [ 9 , 21 ]), its low reactivity, slow oxidation kinetics, small particle size, and low bulk density explain why rCB combustion studies are rarely found.…”
Section: Recovered Carbon Blackmentioning
confidence: 99%
“…Moreover, after further processing [ 68 , 69 ], these activated carbon materials can be employed in a large variety of fields, as depicted in Figure 4 . In recent studies, activated rCB samples were investigated as adsorbents for the separation of compounds in gaseous [ 70 , 71 , 72 ] and liquid [ 73 ] phases (e.g., adsorption of dyes [ 74 , 75 ], organic compounds [ 76 , 77 , 78 , 79 ], and heavy metals [ 80 , 81 , 82 ]), as conductive additives for carbon electrodes of sodium and lithium batteries [ 83 , 84 , 85 , 86 ], as supercapacitors [ 87 ], as catalysts [ 88 , 89 ] and as nanomaterial precursors [ 90 , 91 ]. Even though rCB has been identified as a potential solid fuel (the HHV is within 25 to 34 MJ/kg [ 9 , 21 ]), its low reactivity, slow oxidation kinetics, small particle size, and low bulk density explain why rCB combustion studies are rarely found.…”
Section: Recovered Carbon Blackmentioning
confidence: 99%
“…C K and S K-Edge XANES measurements were conducted on the so X-ray beamline at the Australian Synchrotron 41 following the same procedures outlined in previous work. 12,13,20,21 For normalization of the beam energy between scans all samples were measured simultaneously with TEY of an Au mesh situated in front of the sample (I 0 signal), i.e., sample signal divided by the I 0 TEY signal. For edge energy calibrations, S K-edge spectra of the samples were also simultaneously measured with a MoS 2 reference foil maintained in the beamline with a known absorption edge centered at 2471.2 eV, and a pyrolytic graphite (HOPG) reference foil centered at 291.65 (26) eV for C K-edge spectra.…”
Section: Synthesis Of Poly(s-r-limonene)mentioning
confidence: 99%
“…For C K-edge spectra, normalization to account for contributions from internal carbon contamination of the beamline was achieved by scanning a clean Si photodiode reference following the procedure outlined by Watts et al 42 Calibration and normalization of the C and S K-edge XANES data were performed using the Quick AS NEXAFS Tool (QANT) macro developed for Igor Pro. 43 13 C NMR experiments were performed on a Bruker Biospin Avance III 300 MHz spectrometer equipped with a wide bore 7 T superconducting magnet (75 MHz for 13 C and 300 MHz for 1 H). Aer drying inside an Ar-lled glovebox, approximately 80 mg of as-synthesised copolymer was packed into 4 mm outer diameter zirconia rotors with Kel-F® caps and spun to 6.5 kHz at the magic angle for measurement.…”
Section: Synthesis Of Poly(s-r-limonene)mentioning
confidence: 99%
See 2 more Smart Citations